Legal Review of Tabarru’ Contract in the Refund of Premi in Islamic Insurance - Linda Pratiwi; Uruban Atroba Mubarok (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2024)
This paper explores the legal framework surrounding the refund of tabarru’ funds in Islamic insurance. Tabarru' represents a donation in which participants contribute to a collective fund for mutual assistance. However, the refund of these funds, particularly when participants discontinue their policies, raises questions about its legal permissibility. Using a qualitative juridical-empirical approach, this study reviews Islamic jurisprudence, Indonesian law, and fatwas issued by the National Sharia Council (DSN-MUI). The study finds that while tabarru' is fundamentally a donation, refunds are permissible under specific conditions, particularly when underwriting surpluses are involved. The findings contribute to the ongoing discourse on aligning Islamic insurance practices with Shariah principles while meeting contemporary needs.